Impact of low preoperative appendicular skeletal muscle mass on postoperative complications and short-term outcomes in liver transplant recipients: a propensity score-matched retrospective study - Xu, Jing; Wu, Qian; Xu, Xiaofeng; Weng, Feihong; Lv, Tao; Yang, Jian; Wang, Shouping; Li, Rui; Ai, Chengbo; Xu, Gang; Yan, Lvnan; Yang, Jiayin (Frontiers in Surgery, 2025)
BackgroundLow preoperative appendicular skeletal muscle mass (ASM) is common in liver transplantation (LT) recipients and may be linked to adverse postoperative outcomes. This study explored the relationship between preoperative ASM and short-term postoperative outcomes, including perioperative inflammation.MethodsWe retrospectively analyzed 653 LT patients at West China Hospital from 2015 to 2022. ASM index (ASM/H2) was calculated using Asian Working Group for Sarcopenia (AWGS) standards. Patients were classified into low and non-low ASM groups by sex-specific cutoffs. Propensity score matching (PSM, 1:1) was used to control for confounding. Associations with complications, inflammatory markers, and survival were evaluated using multivariate logistic and Cox regression. The predictive performance was evaluated using receiver operating characteristic (ROC) curves.ResultsAfter PSM, 84 matched pairs were analyzed. On postoperative days 1 and 3, the low ASM group had significantly higher neutrophils, NLR, MLR, and NMR (P < 0.05), and lower lymphocyte and platelet counts. This group also showed increased early complications, including pulmonary infection, pleural effusion, and intra-abdominal bleeding (in-hospital mortality: 9.52% vs. 1.19%, P = 0.040). Low ASM independently predicted complications (OR = 6.61, 95% CI: 3.08–14.21) and worse overall survival (HR = 2.25, 95% CI: 1.41–3.57). Predictive models including ASM achieved high accuracy (AUC = 0.80 for complications; AUC = 0.75 for survival).ConclusionsLow preoperative ASM is an independent risk factor for inflammation, complications, and poorer survival after LT. ASM screening may improve early risk stratification and guide perioperative care.